2016
DOI: 10.3171/2015.5.peds15118
|View full text |Cite
|
Sign up to set email alerts
|

Predicting shunt failure in children: should the global shunt revision rate be a quality measure?

Abstract: OBJECT Ventricular shunts for pediatric hydrocephalus continue to be plagued with high failure rates. Reported risk factors for shunt failure are inconsistent and controversial. The raw or global shunt revision rate has been the foundation of several proposed quality metrics. The authors undertook this study to determine risk factors for shunt revision within their own patient population. METHODS In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Shunting and ventriculostomy are the two permanent treatment methods of CSF diversion. Unfortunately, shunting in the pediatric population is associated with high shunt failure rates/revisions rates ranging from 20% to 85% (Berry et al., 2008 ; Bir et al., 2016 ; Gupta et al., 2007 ; Merkler et al., 2017 ; Reddy et al., 2014 ; Riva‐Cambrin et al., 2016 ; Rossi et al., 2016 ; Stein & Guo, 2008 ; Stone et al., 2013 ; Wu et al., 2007 ). Complication rates in terms of revision surgery have frequently been examined and the literature is extensive.…”
Section: Introductionmentioning
confidence: 99%
“…Shunting and ventriculostomy are the two permanent treatment methods of CSF diversion. Unfortunately, shunting in the pediatric population is associated with high shunt failure rates/revisions rates ranging from 20% to 85% (Berry et al., 2008 ; Bir et al., 2016 ; Gupta et al., 2007 ; Merkler et al., 2017 ; Reddy et al., 2014 ; Riva‐Cambrin et al., 2016 ; Rossi et al., 2016 ; Stein & Guo, 2008 ; Stone et al., 2013 ; Wu et al., 2007 ). Complication rates in terms of revision surgery have frequently been examined and the literature is extensive.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, a single-center university study (n = 341) by Shannon et al reported relatively lower rates of 15% and 21% at 6 and 24 months, respectively, and another study in a children's hospital (n = 466) by Rossi et al reported relatively higher rates of 24.1% and 29.9% at 3 and 6 months, respectively. 17,21 In the United Kingdom, a multicenter database study (n = 1615) by Al-Tamimi et al and a single-center teaching hospital study (n = 321) by Anderson et al reported relatively higher rates at 12 months of 28.8% and 26.0%, respectively. 10,12 Our shunt failure trend showing high failure rates within the first year followed by lower rates over time is consistent with published literature.…”
Section: Discussionmentioning
confidence: 99%
“…11 Evidence on specific etiology associated with shunt failure was mixed. 12,21,27,33 Many studies have identified congenital hydrocephalus as a significant risk factor for initial shunt failure. 11,20,22 In general, patients with hydrocephalus caused by congenital abnormalities are more likely to undergo shunt placement earlier when compared to patients with other etiologies, which may coincide with the notion that younger patients have a higher failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Rossi et al report a 90-day shunt failure rate of 24.1% and a 180-day shunt failure rate of 29.9%. 22 Notably, these rates are for shunts placed for any indication, and may not accurately represent the population of MMC patients with shunted hydrocephalus. Overall, the risk for shunt failure in MMC is highest within the 1st year of life, with declining risk thereafter, except for a spike in the early teenage years.…”
Section: Discussionmentioning
confidence: 99%